Eighth grade [videorecording (DVD)] - Burnham, Bo, 1990-; Fisher, Elsie, 2003-; Hamilton, Josh; Robinson, Emily, 1998- (Lionsgate, 2018)
Thirteen-year-old Kayla endures the tidal wave of contemporary suburban adolescence as she makes her way through the last week of middle school (the end of her thus far disastrous eighth grade year) before she begins high school.